UTILIZATION OF NA2O/LAPINDO MUD NANOCATALYST IN THE TRANSESTERIFICATION REACTION OF USED COOKING OIL INTO BIODIESEL - Hapsari, N. N.; Samik, S. (Jurnal Kimia (Journal of Chemistry); Vol. 19 Issue 2, Juli 2025DO - 10.24843/JCHEM.2025.v19.i02.p20, 2025)
Penelitian ini mendemonstrasikan preparasi Lumpur Lapindo yang diimpregnasi dengan NaOH untuk digunakan sebagai katalis heterogen dalam reaksi transesterifikasi minyak jelantah menjadi biodiesel. Katalis dibuat dengan cara impregnasi NaOH pada Lumpur Lapindo, kemudian dikalsinasi pada suhu 550 °C selama 3 jam. Setelah itu, dilanjutkan proses ball milling dengan kecepatan 4000 rpm selama 1 jam untuk mengubahnya menjadi nanokatalis Na 2 O/LM. Penggunaan nanokatalis ini meningkatkan luas permukaan yang memungkinkan interaksi lebih efektif dengan reaktan, sehingga mempercepat proses katalisis. Karakterisasi nanokatalis dilakukan menggunakan XRF, XRD, FTIR, dan PSA. Mekanisme reaksi transesterifikasi melibatkan minyak jelantah dan metanol dengan rasio 1:9, nanokatalis Na 2 O/LM 5 %wt, reaksi ini berlangsung selama 2 jam pada suhu 65°C. Penggunaan nanokatalis Na 2 O (0) /LM, Na 2 O (20) /LM, Na 2 O (40) /LM dan Na 2 O (60) /LM menghasilkan yield berturut-turut 77,36%; 83,27%; 86,51%; dan 96,68%. Uji kualitas biodiesel mencakup bilangan asam, kadar air, titik nyala, densitas, viskositas, dan GC-MS. Pengujian GC-MS dilakukan pada yield biodiesel terendah Na 2 O (0) /LM dan tertinggi Na 2 O (60) /LM, menghasilkan FAME masing-masing sebesar 99,26% dan 99,99%. Kata kunci: nanokatalis; Na 2 O/LM; minyak jelantah; transesterifikasi; biodiesel ABSTRACT   This research demonstrates the preparation and characterization of NaOH-impregnated Lapindo Mud nanocatalysts for biodiesel production from waste cooking oil through transesterification. The nanocatalysts were synthesized by wet impregnation of NaOH into Lapindo Mud, calcination at 550°C for 3 hours, and ball milling at 4000 rpm for 1 hour to achieve a nanoscale particle size. Enhanced surface area significantly improves reactant-catalyst interaction, accelerating the catalysis process. Characterization using XRF, XRD, FTIR, and PSA revealed systematic changes in chemical composition and structure with increasing NaOH content. XRF analysis showed decreased SiO 2 and increased Fe 2 O 3 levels with higher NaOH percentages, while XRD identified four phases: SiO 2 , Na 2 O, Na 2 SiO 3 , and Al 2 SiO 5 , with Na 2 SiO 3 formed from NaOH-SiO 2 reactions. PSA analysis indicated particle size increases from 514.3 nm [Na 2 O(0)/Lapindo Mud] to 577.7 nm [Na 2 O(60)/Lapindo Mud] due to aggregation. Transesterification reactions were conducted using waste cooking oil and methanol at a 1:9 ratio with 5 wt% nanocatalyst for 2 hours at 65°C. Catalytic performance demonstrated a strong correlation between NaOH content and biodiesel yield: NaOH(0)/Lapindo Mud (77.36%), NaOH(20)/Lapindo Mud (83.27%), NaOH(40)/Lapindo Mud (86.51%), and NaOH(60)/Lapindo Mud (96.68%). GC-MS analysis confirmed excellent biodiesel quality, with FAME content of 99.26% and 99.99% for the lowest and highest performing catalysts, respectively. Results demonstrate that NaOH-impregnated Lapindo Mud nanocatalysts offer a cost-effective and environmentally sustainable solution for converting waste cooking oil into high-quality biodiesel. Keywords : nanocatalysts; Na 2 O/Lapindo Mud; waste cooking oil; transesterification; biodiesel